Decision support for the technician routing and scheduling problem - Gamst, Mette; Pisinger, David (Networks, 2024)
The technician routing and scheduling problem (TRSP) optimizes routes for technicians serving tasks subject to qualifications, time constraints, and routing costs. In the literature, the TRSP is solved either to provide actual technician work schedules or to perform what‐if analyses on different TRSP scenarios. A TRSP scenario consists of a given number of tasks, technicians, skills, working hours and so forth. We present a method which builds optimal TRSP scenarios with respect to technician fleet, their skills, their working hours and digitization of task equipment. The scenarios are built such that the combined TRSP costs (OPEX) and investment costs (CAPEX) are minimized. By using a holistic approach we can generate scenarios that would not have been found by studying the investments individually. The proposed method consists of a matheuristic based on column generation. To reduce computational time, the routing costs of a technician are estimated instead of solved to optimality. The proposed method is evaluated on data from the literature and on real‐life data from a telecommunication company. The evaluation shows that the proposed method successfully suggests attractive scenarios. The method especially excels in ensuring that more tasks are serviced, but also in reducing travel time with around 16% in the real‐life instance. We believe that the proposed method could constitute an important strategic tool for routing companies. In the conclusion, we propose future research directions to extend the applicability.